The context of translation : Richard Fanshawe and Spanish verse - Río, Eduardo R. del (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
Compared to French and Italian, Spanish poetry was almost completely ignored by English translators during the seventeenth century. The limited amount of poetry that was translated, however, reveals important historical and social forces at work. Specifically, the deep resentment and fear that Protestant England held toward the “evil popish forces” of Catholic Spain played an essential role in guiding translators’ choices. This essay examines contemporary accounts of Anglo-Spanish relations in England, and argues that the fear of popery was a determining principle behind the choices of at least one translator of Spanish poetry, Sir Richard Fanshawe. Richard Fanshawe’s interest in Spanish literature, however, was also a personal one. His diplomatic assignments in that country made him acquire a taste for the language and culture of that land. Fanshawe’s close relationship with the Stuart monarchy -a monarchy that itself showed ambivalence toward Spain- is one more factor to consider when attempting to understand his translating choices.